1995
DOI: 10.1021/ic00115a033
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprinting Petroporphyrin Structures with Vibrational Spectroscopy. 3. Resonance Raman Characterization of Regioisomers of Nickel(II) Tetrahydrobenzoporphyrin

Abstract: Nickel(II) complexes of the geochemically significant four regioisomers of tetrahydrobenzoetioporphyrin, NiTHBP-A, -B, -C, and -D, which contain a reduced benzo unit fused onto the Cp atoms of a pyrrole ring, have been synthesized and structurally characterized by resonance Raman (RR) spectroscopy with variable-wavelength excitation. Spectra were obtained from CS2 and CH2Cl2 solution samples at room temperature excited at 406.7, 530.9, and 568.2 nm, in resonance with the porphyrin Soret, Ql, and QO electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 4 publications
1
28
0
Order By: Relevance
“…Baum and Plane [46] studied the pyridine catalysed incorporation of Mg 2 + into deuteroporphyrin dimethyl ester in buffered methanol, and found a term k(H 2 -P)/(H + ) independent of metal ion concentration. One pathway consistent with the data was a rate-limiting dissociation of H 2 -P into H-P -, followed by a fast reaction of the mono-anion with the metal [Eqs (10) and (11)]. Another scheme involved an unknown acid BH (perhaps water) whose anion reacted with H 2 -P in a slow step to form H-P -, which then rapidly reacts with the metal.…”
Section: Metal Ion Incorporation Reactionsmentioning
confidence: 61%
See 1 more Smart Citation
“…Baum and Plane [46] studied the pyridine catalysed incorporation of Mg 2 + into deuteroporphyrin dimethyl ester in buffered methanol, and found a term k(H 2 -P)/(H + ) independent of metal ion concentration. One pathway consistent with the data was a rate-limiting dissociation of H 2 -P into H-P -, followed by a fast reaction of the mono-anion with the metal [Eqs (10) and (11)]. Another scheme involved an unknown acid BH (perhaps water) whose anion reacted with H 2 -P in a slow step to form H-P -, which then rapidly reacts with the metal.…”
Section: Metal Ion Incorporation Reactionsmentioning
confidence: 61%
“…Perhaps due to the earlier complex multistep synthetic pathways [4][5][6] and the low solubilities of the resulting complexes, tetrabenzoporphyrins have received relatively little attention. A one-pot template method now yields gram quantities of Zn-TBP [7], and both ring [8] and meso-substituted species [9,10] have been prepared. Recent work has appeared on Fe [11], Pt [12,13], Pd [12], Zn [6,14], Cd [15], Mg [15], Co [16] and Ge [16] complexes, and ring-oxidized M-TBP iodides [17,18], where M stands for a metal.…”
Section: Introductionmentioning
confidence: 99%
“…Condensation of 15b with diformylpyrrole 12a afforded this system in 42% yield (Scheme 5). Given the smaller number of steps involved, this provides a superior route to this geochemically important series [49,50]. We have demonstrated that tetrahydrobenzoporphyrins are easily dehydrogenated with DDQ in refluxing toluene to give the corresponding benzoporphyrins [49], the 'rhodoporphyrins' from petroleum, and the '3 + 1' route therefore provides access to these structures as well.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we showed 19 that the strongest RR band in the Soret-excited spectrum of (VO)Etios arises from the characteristic vanadyl stretch at 991 cm -1 and that many (VO)Etio high-frequency vibrations associated mainly with pyrrole C β C β and methine bridge C α C m stretching modes have significantly lower (14−28 cm -1 ) frequencies than their corresponding modes in NiEtios, enabling the two petroporphyrin families to be readily distinguished. We have also demonstrated the potential of RR spectroscopy, especially with the porphyrin Q-band absorption excitation, to differentiate petroporphyrin positional isomers via significant differences in the 750−1050 cm -1 alkyl substituent vibrations of NiEtio isomers I−IV. , In another recent study, we established structure marker bands unique to tetrahydrobenzoetioporphyrins, assigned vibrational modes related to the tetrahydrobenzo exocyclic ring, and showed that RR spectroscopy can distinguish petroporphyrin positional isomers possessing the same overall symmetry …”
Section: Introductionmentioning
confidence: 87%
“…The RR spectra were obtained with a Coherent K-2 Kr + ion laser excited at or near the absorption maxima of the porphyrin Soret and Q bands with 406.7 (violet), 530.9 (green), and 568.2 nm (yellow) lines. Essentially all of the Raman-active fundamental modes can be identified in the spectra by using these three excitation wavelengths, as previously demonstrated by studies of Ni complexes of octaethylporphyrin (OEP), meso -tetraphenylporphyrin (TPP), etioporphyrins I−IV, , and four isomeric tetrahydrobenzoporphyrins (THBP) . The scattered photons were collected via backscattering geometry from spinning NMR tubes in solution (∼1 mM in carbon disulfide).…”
Section: Methodsmentioning
confidence: 98%